Avaliação e monitoramento dos contatos intradomiciliares de pacientes com hanseníase: sorologia para detecção de anticorpos anti-PGL-I e avaliação da reatividade a proteínas recombinantes do Mycobacterium leprae - Silva, Eliane Aparecida [UNIFESP] (2016)
Leprosy, a chronic disease with high infectivity and low pathogenicity, manifests by dermato-neurological signs and symptoms and may cause physical disabilities and deformities. The leprosy elimination strategy is based on case detection in the early stages of the disease and the effectiveness of chemotherapy. In order to assist in the diagnosis of the disease, serological tests have been developed. Thus, this study aims to: I. to validate the utility of fusion antigen LID-1 associated with the synthetic disaccharide (ND-O) of phenolic glycolipid-I (PGL-I), in field work; II. to identify the number of leprosy cases diagnosed in Rondonópolis-MT during five years of followup of household contacts at the time of diagnosis of the index case, using clinical and serological exams (IgM anti ND-O-BSA and IgM/IgG anti ND-O-LID-1). In the period from 2009 to 2010, in Rondonopolis-MT, active search for new leprosy cases and their household contacts was carried out. From this work, in the present study we evaluated serum samples, clinical and epidemiological data of diagnosed leprosy cases classified by bacteriological, histological and clinical criteria (n = 174); household contacts who lived with the index cases at diagnosis or in the last five years (n = 409); individuals from endemic areas without diagnosis and family history of leprosy (n = 53); patients diagnosed with pulmonary tuberculosis (n = 12). Household contacts were followed (n = 186) over a five-year period. Blood was collection by venipuncture for serological tests at diagnosis and during follow-up of five years, in addition, dermatological and neurological examination were performed. For enzyme immunoassay for the detection of anti-PGL-I antibody (ND-O-BSA) were considered positive OD ? 0.150 and for the anti-ND-O-LID-1 immunodot positivity was given in crosses (0,5+, 1+, 2+, 3+). Results of antibodies serum levels stratified by clinical form (43 tuberculoid, 63 borderline-tuberculoid, 30 borderline-borderline, 12 borderline-lepromatous, 07 lepromatous, 19 indeterminate) showed higher positivity for the rapid testing in MB patients: 100% for VV and DV, and 73.33% for DD. Individuals PB showed 7.20% positivity to the rapid test. The positivity of anti-PGL-I ELISA among 409 contacts was low (3.17%) and for the anti-ND-O-LID-1 rapid test was 14.66%, with nine positive samples 1+ and 51 positive 0,5+. In the first evaluation, nine (2.20%) contacts were diagnosed with leprosy, six were negative for both serological tests, two 0,5+ for LID-1 and negative for PGL-I and one 1+ to LID -1 and positive to PGL-I. When comparing all patients r2 = 0.8444 correlation was obtained indicating good agreement between the serological tests. Correlation r2 = 0.7382 was found between results of ND-O-LID-1 and bacterial index of MB patients.The results showed that levels of anti-ND-O-BSA antibodies by ELISA correspond to semi-quantitative results of anti-ND-O-LID-1 in the rapid test. Clinical examination of household contacts proved to be a good procedure for active case finding, as it detected new leprosy cases in 2.2% of examined contacts. The followup of household contacts for five years made possible the detection of 3.22% of new cases among contacts. The quantification of anti-ND-O-BSA by ELISA can be used as a laboratory tool to indicate exposure to M. leprae in contacts. Positive serology may indicate infection with M. leprae, without necessarily evolution to disease. All these observations allowed us to conclude that individuals with positive serology should be followed for longer periods than recommended by the control program.